Pengembangan E-Modul Matematika Pada Materi Pecahan - Lale Nadia Kadar Maniq; I Nyoman Karma; Awal Nur Khalifatur Rosyidah (Program Studi Magister Pendidikan IPA, Universitas Mataram, 2022)
This research aims to produce learning resources in the form of mathematics e-modules to be tested for eligibility in students of grade IV SDN 2 Batujai. The type of research used in research is development research with 4d models (Define, Design, Develop, and Disseminate). The subjects used in this study were teachers and students of grade IV at SDN 2 Batujai which numbered 29 people. The results showed that learning resources in the form of e-module mathematics already met the criteria worthy by obtaining a percentage of 79,7% of material experts and 85% of media experts. Teacher response and student response showed that the mathematics e-modules were feasible to use with 82,5% of teacher responses and 84,2 % of student responses. Based on the data it can be concluded that e-module mathematics fractional material is suitable for use as a source of learning that can be used by students and teachers